Analysis on indonesia strategic framework to face asean 5 in asean free trade area (AFTA) 2015 - Koesrindartoto, Deddy P; Suryanta, Barli (Jurnal Manajemen Teknologi, 2010)
This paper has purpose to assess Indonesia readiness of sectors to face ASEAN 5, those are Brunei, Malaysia, Philippines, Singapore, and Thailand in near AFTA2015. And also this paper want to construct the compatible Indonesia's strategic framework that it will be useful for Indonesia itself in order to be key player in AFTA 2015. Furthermore, the econometric approach by using gravity equation model will be applied to assess Indonesia readiness to face AFTA2015 which using mechanism of free flows of goods.Keywords: AFTA2015, Indonesia Strategic Framework, Gravity Equation Model